Pregnancy and portal hypertension a pathology view of physiologic changes - Eric Lopez-Mendez; Lourdes Avila-Escobedo (Annals of Hepatology, 2006)
The coexistent of pregnancy and liver disease represent a complex clinical situation, besides the liver complications that present in pregnancy with a previous health liver, like intrahepatic cholestasis of pregnancy, acute fatty liver of pregnancy or HELLP syndrome with bleeding disorders and viral hepatitis, the previous liver damage with portal hypertension associated represent a clear stated of hemodynamic changes which increased risk of variceal bleeding. The portal hypertension syndrome has a splanchnic blood flow increase. During pregnancy an hypervolemic stated developed as consequence there is an increased in portal flow that contributed to more portal pressure transmitted to the collaterals veins which increase variceal bleeding risk in this group of patients. The present review will focus on treatment options to prevent variceal bleeding in this clinical situation.